Meningkatkan Hasil Belajar Siswa Melalui Metode Make A Match Pada Meneladani Asmaul Husna Kelas V UPTD SDN 01 Piobang - Sri Hardina; Nelvi Yerni; Alhusni Fuad; Roza Elfira; Fadhila Yusri; Adi Warman (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve student learning outcomes in the material Emulating Asmaul Husna by applying the make a match learning method in class V UPTD SDN 01 Piobang with the variables that are the target of change in this study are learning outcomes, while the action variables used in this study are the make a match learning method. This research is classroom action research carried out in 2 cycles, each cycle consisting of 4 stages, namely planning, implementation/action, observation/observation, and reflection. The data collection techniques used are observation/observation, interviews, documents and tests. Based on the results of the study, it can be concluded that student learning outcomes continue to increase until they reach a significant increase. Student learning outcomes at the pre-action stage were 40%, in cycle I (first) increased to 60% in cycle II (second) also increased to 90%. Thus, a recommendation can be submitted that the application of the make a match learning method can improve student learning outcomes in the material Emulating Asmaul Husna for the 2024/2025 Academic Year.: